Quality analysis of the environmental impact report of a port terminal in the Municipality of Itacoatiara/AM (Research, Society and Development, 2021)
This study aimed to carry out a qualitative analysis of the environmental impact report (RIMA) of a port terminal located in the municipality of Itacoatiara/AM. The report was analyzed according to the minimum parameters established by Article 9 of CONAMA Resolution No. 01/1986, which provides for minimum criteria for preparing the RIMA. A general synthesis of the analyzed requirements was carried out. It was possible to observe that the report has several technical words that make understanding and clarity difficult. RIMA presents coherent objectives and justifications, with excellent quality. In this way, the alternatives and the environmental diagnosis of the project are mostly in accordance with the CONAMA Resolution. On the other hand, there is a deficiency in environmental impacts, which are not characterized in the installation and operation phases. The different situations and their alternatives were not considered, as well as the non-execution of the project. The mitigating measures are presented in a clear and objective way, but not enough programs were presented. Finally, the conclusion is not consistent with the reality of the project, as well as the multidisciplinary team, where there is not a variety of professionals. Overall, 60% of the requirements highlighted by the CONAMA Resolution were not in agreement, while 40% were relatively within the recommendations. Thus, this study presents data that show the quality of RIMA that, in the absence of this information, damage to the environment is possible, as well as a lack of understanding for the lay public.